THE INFLUENCE OF COMMUNICATION PATTERNS, ORGANIZATIONAL CULTURE AND REWARDS ON IMPROVING EMPLOYEE PERFORMANCE AT PT BAKRIE SUMATRA PLANTATION KISARAN - Alfina, Shinta Rizki; Mardhiyah, Ainun (Transpublika Publisher, 2023)
The success of a company relies heavily on employee performance, making it crucial to consider employee performance when aiming to improve overall company performance. Communication patterns and organizational culture play vital roles in this regard, as effective communication within the company and a positive organizational culture can enhance employee performance. This study investigates the impact of communication patterns, organizational culture, and rewards on improving employee performance at PT. Bakrie Sumatra Plantation Kisaran. The study employs a quantitative research approach with an associative focus. The sample consists of 40 respondents selected through saturated sampling. Primary data was collected using questionnaires distributed directly to the respondents, employing a Likert scale. The data analysis involves instrument validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS. The findings indicate a strong relationship between communication patterns, organizational culture, rewards, and employee performance, as evidenced by a coefficient of determination (R2) of 0.668. Furthermore, the variables of communication patterns, organizational culture, and rewards explain and affect employee performance (Y) by 0.399, as indicated by the coefficient of determination (Adjusted R Squared). This study reveals that communication patterns (X1), organizational culture (X2), and rewards (X3) significantly influence employee performance (Y) at PT. Bakrie Sumatra Plantation Kisaran, while 60.1% of the variance in employee performance is attributed to other unexplored factors.